Alternative evaluation of voltage at top of transmission line tower stricken by lightning - Yevgeniy Trotsenko (Technology Audit and Production Reserves, 2021)
The object of the research is a circuit that simulates a lightning strike to a tower of 220 kV power transmission line, taking into consideration the reflection of a current wave from 10 nearest towers. Computation of the voltage arising at the top of the stricken tower is necessary further to determine the lightning performance of transmission line by various methods. For Indian conditions, the average number of lightning strikes to this power line per 100 kilometers per year is about 77, which is a fairly high figure. As a rule, for the tasks of lightning protection, the lightning current is approximated by some analytical expression. In most cases, such expressions are various combinations of exponential functions. However, the waveform of real lightning currents on oscillograms differs significantly from the waveform attributed to them and approximated by relatively simple exponential expressions. For a more detailed study of transient processes caused by thunderstorm activity, there is a need to use oscillograms of real lightning currents when modeling.